Have You Benefited from the Tax Reforms? The Distribution of Tax Payments in Sweden after Three Decades of Tax Changes - Åsa Hansson (Research Institute of Industrial Economics (IFN), 2020)
Thirty years ago, the Swedish tax system underwent a major reform. Since then there have been many changes to the tax system, and the general level of tax revenues has declined by over five percentage points of GDP. The decline in total revenues does not necessarily translate into an evenly distributed decline for taxpayers. This paper studies how tax payments have changed in Sweden since the major tax reform over income distribution, sex, age, and geographical location. The results show that individuals at the bottom and very top of the income distribution have benefited disproportionally more from lower taxes. Labor tax payments as share of labor income have increased across the income distribution and particularity so for middle- and high-income earners.
Keywords: D63; H23; H24; 330; Tax burden; Tax distribution; Tax reform